(untitled) (Swiss Medical Weekly, 2022)
AIMS OF THE STUDY: Clinical teaching is essential in preparing trainees for independent practice. To improve teaching quality, clinical teachers should be provided with meaningful and reliable feedback from trainees (bottom-up feedback) based on up-to-date educational concepts. For this purpose, we designed a web-based instrument, "Swiss System for Evaluation of Teaching Qualities" (SwissSETQ), building on a well-established tool (SETQsmart) and expanding it with current graduate medical education concepts. This study aimed to validate the new instrument in the field of anaesthesiology training. METHODS: Based on SETQsmart, we developed an online instrument (primarily including 34 items) with generic items to be used in all clinical disciplines. We integrated the recent educational frameworks of CanMEDS 2015 (Canadian Medical Educational Directives for Specialists), and of entrustable professional activities (EPAs). Newly included themes were "Interprofessionalism", "Patient centredness", "Patient safety", "Continuous professional development’, and "Entrustment decisions". We ensured content validity by iterative discussion rounds between medical education specialists and clinical supervisors. Two think-aloud rounds with residents investigated the response process. Subsequently, the instrument was pilot-tested in the anaesthesia departments of four major teaching hospitals in Switzerland, involving 220 trainees and 120 faculty. We assessed the instrument’s internal structure (to determine the factorial composition) using exploratory factor analysis, internal statistical consistency (by Cronbach’s alpha as an estimate of reliability, regarding alpha >0.7 as acceptable, >0.8 as good, >0.9 as excellent), and inter-rater reliability (using generalisability theory in order to assess the minimum number of ratings necessary for a valid feedback to one single supervisor). RESULTS: Based on 185 complete ratings for 101 faculty, exploratory factor analysis revealed four factors explaining 72.3% of the variance (individual instruction 33.8%, evaluation of trainee performance 20.9%, teaching professionalism 12.8%; entrustment decisions 4.7%). Cronbach’s alpha for the total score was 0.964. After factor analysis, we removed one item to arrive at 33 items for the final instrument. Generalisability studies yielded a minimum of five to six individual ratings to provide reliable feedback to one supervisor. DISCUSSION: The SwissSETQ possesses high content validity and an "excellent" internal structure for integrating up-to-date graduate medical education concepts. Thereby, the tool allows reliable bottom-up feedback by trainees to support clinical teachers in improving their teaching. Transfer to disciplines other than anaesthesiology needs to be further explored.